Evaluating the Implementation of Suicide Prevention Policy in Gunungkidul Regency: A Van Meter and Van Horn Model Analysis - Lintang Ciptaning Tyas; Wahyu Beny Mukti Setiawan (Transpublika Publisher, 2026)
Suicide in Gunungkidul Regency is a persistent public policy problem, affected by institutional and socio-cultural factors. This study measures the implementation of the suicide prevention policy contained in Regulation No. 18 of 2022 using Van Meter and Van Horn. Using a qualitative approach, through interviews, observations, and document analysis. The results show that policy implementation remains suboptimal, not only due to a separate constraint but also due to the interaction of weak operational standards, resource constraints, fragmented interorganizational communication, and socio-cultural barriers. The model highlights systemic gaps, including the lack of a localized Regional Action Plan, an imbalance in resource allocation between curative and preventive services, and inadequate cross-sectoral coordination. Additionally, the stigma surrounding mental health and the persistence of the Pulung Gantung myth further hinder early detection and community engagement. This study contributes by illustrating how the interaction between institutional capacity and the local socio-cultural context affects policy outcomes in a decentralized setting. Enhancing context-specific policy instruments and aligning cross-sectoral coordination are crucial for improving implementation effectiveness.